THE EFFECTIVENESS OF VOCABULARY GAMES IN ENGLISH GRAMMAR CLASS - Lungguh Halira Vonti; Abdul Rosyid (Pedagonal : Jurnal Ilmiah Pendidikan, 2019)
ABSTRACTThe study is aimed to investigate the effectiveness of giving vocabulary game on students' ability in grammar class. The study was conducted to the first semester of English Education Study Program students in Faculty of Teachers Training and Educational Sciences, Pakuan University.The population of the study is the first semester students of the English Department, Faculty of Teachers Training and Educational Sciences, Pakuan University.  From the population, the sample of the study is one experimental class consisted of 25 students. The method of the study is quasi experimental research.  The instruments used by the researcher are test and non test.  The test instruments are questions about tenses and the non test is in forms of questionnaire. From the study, it can be concluded that the students’ ability in using new verbs in constructing sentences based on tenses taught  has significantly been increased.  It is shown from the high score of students’ test. The calculatation of df (degree of freedom) is gained from df = (N-1) = 11-1 = 10 and concern with the t table value with df = 11, the value of tt table degree of significance 5% is compared to t0.  The t-table is 2.21 and with tt T0 =11,2 which is greater than tt=2,04 we can see that H0 is rejected so there are significant differences between pre-test and post-test. Based on the data calculation above, it is found out that there are significant differences mean between pre-test and posttest. Therefore, the writer concludes that the use of throwing words games as one of vocabulay games is effective in teaching grammar. Keywords: vocabulary games, grammar ABSTRAK Penelitian ini bertujuan untuk mengetahui tingkat efektivitas pemberian permainan kosakata terhadap kemampuan mahasiswa dalam kelas tata bahasa. Penelitian dilakukan terhadap mahasiswa semester satu  Program Studi Pendidikan Bahasa Inggris di Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pakuan. Populasi penelitian adalah mahasiswa semester satu Program Studi Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan. Sample dalam penelitian ini adalah satu kelas experimen yang terdiri dari 25 orang mahasiswa.  Metode penelitian yang digunakan adalah quasi experimental. Instrument dalam penelitian ini adalah tes dan non tes. Instrument yang berupa tes adalah soal mengenai tenses sedangkan non tes berupa kuesioner. Berdasarkan hasil temuan, dapat disimpulkan bahwa kemampuan mahasiswa dalam menggunakan kata kerja baru dalam membuat kalimat berdasarkan tenses yang diajarkan mengalami peningkatan secara signifikan. Hal ini terlihat dari nilai tes mahasiswa yang termasuk tinggi. Perhitungan df (derajat bebas) diperoleh dari  df = (N-1) = 11-1 = 10 dengan nilai tt table dan df = 11, nilai derajat signifikan t table 5% dibandingkan dengan t0. Nilai t-table adalah 2.21dan dengan tt T0 =11,2 yang nilainya lebih besar dari tt=2,04. Dengan demikian dapat dilihat bahwa H0 ditolak sehingga disimpulkan terdapat perbedaan yang signifikan antara pre tes dan post tes. Berdasarkan perhitungan data tersebut, ditemukan perbedaan mean yang signifikan antara pre tes dan post tes.  Oleh karena itu, dapat disimpulkan bahwa penggunaan permainan lempar kata efektif dalam pembelajaran tata bahasa.  Kata kunci: Permainan kosakata, tata bahasa